1972
DOI: 10.1002/aic.690180139
|View full text |Cite
|
Sign up to set email alerts
|

Observations of early turbulence in the pipe flow of drag reducing polymer solutions

Abstract: Early turbulence has for the first time been observed in the flow of very dilute polymer solutions in tubes larger than capillary size. Flow rate-wall shear stress measurements were conducted in 0.553 and 0.660 cm. diameter pipes. Polyethylene oxide samples of two molecular weights were employed, ditsolved in water-glycerine mixtures with viscosities ranging from 0.0261 to 0.160 poise. The flow rate-wall shear stress relationship for these solutions corresponded to Poiseuille's Law below a well-defined onset w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

1973
1973
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 10 publications
(1 reference statement)
3
18
1
Order By: Relevance
“…While the pioneering work by Virk (1975b) found transition in pipe flow of dilute polymer solutions to occur roughly at the same Re as the Newtonian transition, there have been reports of a delayed transition (Giles & Pettit 1967;Castro & Squire 1968;White & McEligot 1970). Significantly, there have also been several reports of 'early turbulence', wherein transition is reported at a Re as low as 500 (Goldstein et al 1969;Forame et al 1972;Hansen et al 1973;Hansen & Little 1974;Hoyt 1977;Zakin et al 1977), although these early experimental efforts were not corroborated and followed up in a systematic manner. The conflicting conclusions of delayed or early transition could perhaps be attributed to poor characterization of the polymer solutions used.…”
Section: Early Transition and Eitmentioning
confidence: 99%
“…While the pioneering work by Virk (1975b) found transition in pipe flow of dilute polymer solutions to occur roughly at the same Re as the Newtonian transition, there have been reports of a delayed transition (Giles & Pettit 1967;Castro & Squire 1968;White & McEligot 1970). Significantly, there have also been several reports of 'early turbulence', wherein transition is reported at a Re as low as 500 (Goldstein et al 1969;Forame et al 1972;Hansen et al 1973;Hansen & Little 1974;Hoyt 1977;Zakin et al 1977), although these early experimental efforts were not corroborated and followed up in a systematic manner. The conflicting conclusions of delayed or early transition could perhaps be attributed to poor characterization of the polymer solutions used.…”
Section: Early Transition and Eitmentioning
confidence: 99%
“…To complicate matters even further, transition Reynolds numbers have been found that are smaller than the Newtonian minimum of approximately 2300 and for this phenomenon the term 'early turbulence' has been coined. For instance, transition Reynolds numbers as low as 500 have been reported (Forame, Hansen & Little 1972;Zakin, Ni & Hansen 1977;Li & McCarthy 1995). Another result is given by Paterson & Abernathy (1972) who found that for a pipe inlet with squared corners polymers do not change the transition Reynolds number.…”
Section: Introductionmentioning
confidence: 96%
“…From birefringence, shear recovery, or normal stress measurements, we can evaluate GS, the stored free energy/cc of homogeneous flowing solutions ( 6 3 , Treating this as an added contribution to the free energy of mixing, we obtain an estimate for the free energy of mixing in flow AG'm = AG, t GS (1)…”
Section: 12)mentioning
confidence: 99%
“…How the flow will perturb these relationships is not obvious. One approach to the problem would be to assume that equilibrium relationships apply with the free energy of mixing given by (1). This would lead to relationships among partial derivatives of AG, and G S which could be tested by experiment.…”
Section: 12)mentioning
confidence: 99%